2012
DOI: 10.1111/j.1462-2920.2012.02774.x
|View full text |Cite
|
Sign up to set email alerts
|

The metagenome of the marine anammox bacterium ‘Candidatus Scalindua profunda’ illustrates the versatility of this globally important nitrogen cycle bacterium

Abstract: Anaerobic ammonium-oxidizing (anammox) bacteria are responsible for a significant portion of the loss of fixed nitrogen from the oceans, making them important players in the global nitrogen cycle. To date, marine anammox bacteria found in marine water columns and sediments worldwide belong almost exclusively to the ‘Candidatus Scalindua’ species, but the molecular basis of their metabolism and competitive fitness is presently unknown. We applied community sequencing of a marine anammox enrichment culture domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
244
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(256 citation statements)
references
References 80 publications
6
244
1
5
Order By: Relevance
“…DNRA is the likely pathway for NO 3 Ϫ reduction to NH 4 ϩ via NO 2 Ϫ , as previously demonstrated by anammox bacteria other than "Ca. Brocadia sinica" (21,22,51). Indeed, we found that "Ca.…”
Section: Discussionmentioning
confidence: 70%
“…DNRA is the likely pathway for NO 3 Ϫ reduction to NH 4 ϩ via NO 2 Ϫ , as previously demonstrated by anammox bacteria other than "Ca. Brocadia sinica" (21,22,51). Indeed, we found that "Ca.…”
Section: Discussionmentioning
confidence: 70%
“…4), dominate the gene expression libraries in the upper oxic waters (50 m), in the lower oxic zone (85 m), and in the transition zone (110 m). Transcripts of these aerobic organisms, however, are essentially absent in the core of the open-ocean AMZ at 200 m, where sequences matching the anammox bacterium "Candidatus Scalindua profunda" (30) are prominent (Fig. 3).…”
Section: How Does Aerobic Metabolism Vary With Time and Space In Amzs?mentioning
confidence: 99%
“…Kuenenia stuttgartiensis' by Strous et al (2006) and Pearson et al, (2007), and in the genome of 'Ca. Scalindua profunda' by van de Vossenberg et al (2013). Thus, anammox bacteria are capable of synthesising hopanoids, including BHT, in anoxic environments.…”
Section: Introductionmentioning
confidence: 99%